The Tempat Sampah Pintar Berbasis Arduino Uno Untuk Madrasah Nurul Iman - Muhammad Haydar Al Ghifary; Arif Rosyid Prasetyio; Komarudin Purnama; Muhammad Hasby Fathurrizqi (Jurnal Ilmiah Teknologi Infomasi Terapan (JITTER), 2023)
A trash can is a place to temporarily store trash, which is usually made of plastic. The way trash cans work is generally quite simple, namely by putting trash in the head of the can. This did not entice the Nurul Iman Madrasah students to throw garbage in the trash and litter the environment around the madrasa. Not to mention, when opening a trash can, you have to use your hands, so the head of the trash can becomes unhygienic and can increase the potential for spreading disease or viruses. For this reason, by adding some technology to a trash can, the trash can can be transformed into a "smart trash can." It is hoped that this can make the activity of disposing of trash even more interesting and more hygienic because children only need to approach the trash can and the trash can will open by itself. The technology used is the Arduino microcontroller, which is the brain of this system, and the HC-SR04 sensor, an ultrasonic sensor.